Anatomopathological and Immunohistochemical Profile of Gliomas of Patients in the Region of Maringá-PR - Valadares, Adriana Domingues (2021)
Introduction: Gliomas represent 80% of the central nervous system tumors. World Health Organization (WHO) has added, in 2016, molecular features to the classification of gliomas. The pathophysiology and risk factors of these tumors are not yet fully understood. Objective: Perform a retrospective analysis of immunohistochemical and anatomopathological reports of gliomas. Method: Cross-sectional, retrospective and descriptive study carried out from anatomopathological and immunohistochemical exams made between January 2014 and December 2018 in a pathological anatomy laboratory in the city of Maringa-PR. Of the 234 reports related to the term glioma, 204 were selected for this study. Results: Astrocytic, ependymal and oligodendroglial tumors were found, with astrocytomas accounting for the majority (86.8% of the cases found). Mean age at diagnosis was 51.8 years and the prevalence was higher in men. Furthermore, immunohistochemically detectable mutations were analyzed, such as p53 (mutated in 66.7% of those tested), isocitrate dehydrogenase (IDH) (28.6% mutated), X-linked alpha-thalassemia mental retardation (ATRX) (21.0%) and diagnostic markers such as positive epithelial membrane antigen (EMA) in all analyzed ependymomas. Conclusion: The necessity of further researches on gliomas is undeniable , both epidemiologically considering the new classification and within the clinical and pathophysiological scope in order to improve the understanding of the pathology and the treatment for the patients.